Aggregate ceramic films produced at room temperature by press forming. Issue 6 (4th February 2020) - Suzuki, Muneyasu; Kusaka, Yasuyuki; Tsuchiya, Tetsuo; Ushijima, Hirobumi; Akedo, Jun
Abstract: Recently, the demand for flexible or stretchable Internet‐of‐things devices has increased with the rise in popularity of wearables. Also, research is progressing for the development of oxide‐based all‐solid‐state lithium‐ion batteries, which are expected to have improved safety and performance compared with current batteries. Room‐temperature processes for the production of oxide films would facilitate the development of such novel devices. Press forming is a simple room‐temperature process; however, conventional press forming cannot produce highly dense green compacts. Here, we developed a new press forming‐based, room‐temperature process, the mega‐press forming (MF) method, that produces highly dense aggregate oxide films at a pressure below 1 GPa, which is lower than that at which oxide particles fracture, by taking advantage of the differences in cohesive force between microsized and nanosized particles. We used our novel process to produce highly dense lead zirconate titanate aggregate films on aluminum foil at room temperature, and found that when impregnated with silicone oil, these films exhibited low leakage current density and saturated polarization hysteresis properties. Furthermore, we were able to produce films with a porosity of only 6%, which is much lower than that of films produced by conventional press forming (20%). Thus, the MF method will be useful for the development of novel functional composite ceramics that are difficult to fabricate using high‐temperature processes.